Cortical thickness, white matter hyperintensities, and cognition after stroke. Issue 1 (January 2020) - Dickie, David Alexander; Gardner, Kirstyn; Wagener, Annika; Wyss, Annick; Arba, Francesco; Wardlaw, Joanna M; Dawson, Jesse; ,
Background: A thinner cerebral cortex is associated with higher white matter hyperintensity burden and cognitive impairment in community-dwelling and dementia cohorts. It is important to assess these associations in people with ischemic stroke because their cerebrovascular disease profiles are different to these cohorts. Aims: We aimed to determine whether cortical thickness was related to white matter hyperintensity burden and cognition after ischemic stroke. Methods: We measured cortical thickness using advanced normalization tools' "KellyKapowski" function in 244 patients with ischemic stroke or transient ischemic attack from the Virtual International Stroke Trials Archive. We measured white matter hyperintensity burden via quantitative volumes and Fazekas score. We extracted data on vascular risk factors at baseline and Mini Mental State Examination scores at one year. We assessed associations between imaging and clinical data using correlation and multiple linear regression. Results: Pairwise correlation showed that higher white matter hyperintensity Fazekas score was associated with a thinner cortex (rho = −0.284, P  < 0.0001). White matter hyperintensities were generally distributed adjacent to and above the lateral ventricles. Voxel-wise analyses showed statistically significant negative associations between cortical thickness and white matter hyperintensities across fronto-temporal and inferior parietal cortical regions. Mean cortical thickness was positively related to Mini Mental State Examination in pair-wise correlation (r = 0.167, P = 0.0088) but there was no independent association after adjustment for age and white matter hyperintensities (beta = 0.016, P = 0.7874). Conclusions: Cortical thickness was not an independent predictor of cognition after ischemic stroke. Further work is required to understand how white matter hyperintensities are associated with a thinner cortex in temporal regions but less so in more superior regions where white matter hyperintensities are generally found in people with stroke.